Mirtazapine for chronic breathlessness? A review of mechanistic insights and therapeutic potential. (1st February 2019) - Lovell, N.; Wilcock, A; Bajwah, S; Etkind, S. N.; Jolley, C. J.; Maddocks, M; Higginson, I. J.
ABSTRACT: Introduction : Chronic breathlessness is a common and distressing symptom of advanced disease with few effective treatments. Central nervous system mechanisms are important in respiratory sensation and control. Consequently, drugs which may modify processing and perception of afferent information in the brain may have a role. Antidepressants have been proposed; however, current evidence is limited. Of potentially suitable antidepressants, mirtazapine is an attractive option given its tolerability profile, low cost, and wide availability, along with additional potential benefits. Areas covered : The paper provides an overview of the physiology of breathlessness, with an emphasis on central mechanisms, particularly the role of fear circuits and the associated neurotransmitters. It provides a potential rationale for how mirtazapine may improve chronic breathlessness and quality of life in patients with advanced disease. The evidence was identified by a literature search performed in PubMed through to October 2018. Expert opinion : Currently, there is insufficient evidence to support the routine use of antidepressants for chronic breathlessness in advanced disease. Mirtazapine is a promising candidate to pursue, with definitive randomized controlled trials required to determine its efficacy and safety in this setting.